Efek Musik dan Stimulasi Auditori Pranatal pada Kemampuan Bahasa Anak Usia Dini - Khusnul Khotimah (Early Stage, 2026)
Language development in early childhood is crucial for communication, cognition, and social interaction. However, not all children experience optimal language growth, often due to a lack of stimulation during the prenatal period. Research has shown that language ability is not only formed after birth but can also be stimulated prenatally through specific auditory inputs. In Indonesia, there is a long-standing tradition of playing classical music, Qur’anic recitations (murottal), and maternal voices to the fetus to stimulate sensory and cognitive development. Despite this, public understanding of prenatal auditory stimulation remains limited. This study aims to raise awareness among parents and communities about the importance of auditory stimulation during pregnancy in supporting children’s language development. The method used is a literature review with a descriptive-analytic qualitative approach, analyzing various scientific sources from the past ten years. The focus is on five forms of prenatal auditory stimulation: classical music, murottal, traditional music, maternal voice, and active parental involvement. Findings indicate that such stimulation significantly affects the readiness of the auditory system and language centers in the brain. Classical music stimulates cognitive areas, murottal provides rhythmic phonetic and spiritual patterns, and the mother’s voice strengthens emotional bonds and activates language areas. These elements work synergistically to build the neurological foundation for more rapid and natural language development. In conclusion, prenatal auditory stimulation is not only a cultural tradition but also a scientifically supported method that should be consciously and systematically implemented, rooted in cultural and spiritual values from the earliest stages of life.